ЗМІСТОВА НАПОВНЕНІСТЬ КАТЕГОРІЇ “ЕМОЦІЙНА КУЛЬТУРА ОСОБИСТОСТІ” В СУЧАСНИХ ПЕДАГОГІЧНИХ ДОСЛІДЖЕННЯХ (Педагогіка вищої та середньої школи, 2022)
The author of the article considérés the essence of the category “emotional culture ”. A brief analysis of pedagogical writing in the given problem is adduced in the article.